Research on application of twisted oval tubes in rod‐baffle heat exchangers. Issue 3 (5th April 2022) - Zhou, Aimin; Liu, Yuce; Sun, Lijuan
Abstract: To enhance the flow and heat transfer in the shell side of rod‐baffle heat exchangers (RBHXs), twisted oval tubes were proposed to be installed in RBHXs. The shell‐side performance was compared of RBHXs with circular tubes or twisted oval tubes of different structural parameters (ratios of long to short axes R and twisted pitches S ). The results show that not all RBHXs with twisted oval tubes of any configuration parameter is better than RBHXs with circular tubes. When the Re is lower, the ratio of long to short axes R is bigger and the twisted pitch S is smaller; RBHXs with twisted oval tubes are more possible to be better than circular tubes. For both heat exchangers, the effects of clamping methods of tubes, one tube by one rod (OTBOR) and one tube within two rods (OTWTR), and baffle distance L b were studied. The results show that Nu and f of OTBOR are both smaller than OTWTR. The comprehensive performance Nu / f 1/3 of OTBOR is 10.65% better than OTWTR for both heat exchangers. With the increase of baffle distance L b, Nu and f decrease; however, Nu / f 1/3 increases by 7.13% and 12.30% for circular tubes and twisted oval tubes, respectively.